Development of a Sensitive and Cost-Effective MWCNTs/CCE Sensor for Electrochemical Determination of Prednisolone in Pharmaceuticals and Blood Serum; Chemosensors; Vol. 13, iss. 12 - Lipskikh M. V. Maksim Vladimirovich; Korotkova E. I. Elena Ivanovna; Erkovich A. V. Alina Vadimovna; Mamina M. S. Margarita Sergeevna; Saqib M. Muhammad; Lipskikh O. I. Olga Ivanovna; Kar P. K. Pradip (2025, 2025)
A sensitive and cost-effective voltammetric sensor using a carbon-containing electrode (CCE) with a renewable surface modified with multi-walled carbon nanotubes (MWCNTs) was developed for the determination of prednisolone in pharmaceuticals and blood serum. The morphological effects of the functionalization process on the MWCNTs were investigated by transmission electron microscopy (TEM). Analysis of the micrographs indicated that the functionalized nanotubes exhibited a higher density of surface defects and a reduced tendency to form bundles compared to their pristine counterparts. Energy dispersive spectrometry (EDS) confirmed that residual iron particles were removed from the MWCNTs during acid functionalization, demonstrating their intrinsic conductivity. The MWCNTs/CCE was characterized by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The electrochemical behavior of prednisolone in Britton–Robinson buffer at the MWCNTs/CCE was investigated by linear sweep cathodic voltammetry, while the quantitative determination was performed by differential pulse voltammetry (DPV). Under optimal conditions, the sensor exhibited a linear concentration range from 0.04 to 0.6 μM with a detection limit of 8 nM. The proposed method was successfully applied in the determination of prednisolone in pharmaceutical formulations and blood serum